Adjustment of Babies to Daycare:: Aspects that Facilitate Adjustment or not - Bossi, Tatiele Jacques; Brites, Sílvia de Andrade Neves Dias; Piccinini, Cesar Augusto (Paidéia (Ribeirão Preto), 2018)
For many children, daycare is the first regular experience of receiving non-maternal care, so that special attention should be paid to the adjustment period. This study’s objective was to investigate, from the mothers’ perspectives, the aspects that facilitated or did not facilitate the adjustment of six-month-old babies to daycare. Twenty mothers participated in this study. They were interviewed one month after their babies started attending a daycare facility. The answers were examined using qualitative content analysis. The factors that potentially facilitated adjustment included: the mothers’ peace of mind; the babies’ individual characteristics; and the caregivers’ qualification. Aspects that did not facilitate adjustment were insecurity on the part of mothers and if the babies became ill. The results reveal how complex adjustment of six-month-old babies to daycare can be, as aspects concerning child development, the relationship established between mother and infant and between caregiver and infant, as well as the dynamics of the daycare center itself, are involved.